É preciso adaptar o ensino às características do aluno: análise histórica de um enunciado - Ana Laura Godinho Lima (Universidade Federal de Uberlândia, 2017)
O artigo efetua uma análise do enunciado segundo o qual é preciso adaptar o ensino às características dos alunos. Essa afirmação expressa um consenso no campo educacional e é recorrente nos discursos da psicologia difundidos nas escolas normais e cursos superiores de educação desde o início do século XX. O trabalho baseia-se no exame de 24 manuais de psicologia para a formação docente publicados no Brasil entre 1900 e 2014. Recorre à perspectiva foucaultiana de análise do discurso e às produções de Nikolas Rose sobre as relações entre a psicologia e a administração social. A análise evidencia que o enunciado em questão associa-se à pressuposição da desigualdade das inteligências e à convicção de que o governo dos homens deve basear-se no conhecimento científico da natureza humana.  "Teaching must be adapted to the charactristics of the student: historical analysis of a statement" Abstract The article analyzes the statement according to which the teaching needs to be adapted to the characteristics of the students. This statement expresses a consensus in the educational field and is recurrent in the discourses of psychology spread in normal schools and higher education courses since the beginning of the twentieth century. The work is based on the examination of 24 manuals of psychology for teacher education published in Brazil between 1900 and 2014. It relies on the Foucaultian perspective of discourse analysis and the productions of Nikolas Rose on the relations between psychology and social administration. The analysis shows that the statement in question is associated with the presupposition of the inequality of the intelligences and the conviction that the government must be based on the scientific knowledge of human nature. Keywords: psychology and education; teacher training; teaching of psychology. "La ensenãnza debe adaptar-se a las características del alumno: análisis histórico de un enunciado" Resumen El artículo hace un análisis de la declaración según la cual es necesario adaptar la educación a los estudiantes. Esta frase expresa un consenso en el campo educativo y es recurrente en el discurso de la psicología generalizada en las escuelas regulares y cursos de educación superior desde el comienzo del siglo XX. El trabajo se basa en el examen de 24 libros de texto de psicología para la formación de profesores publicados en Brasil entre 1900 y 2014. Se utiliza la perspectiva foucaultiana de análisis y producción de Nikolas Rose discurso sobre la relación entre la psicología y la administración social. El análisis muestra que la declaración en cuestión se asocia con la asunción de la desigualdad de la inteligencia y la convicción de que el gobierno debe basarse en el conocimiento científico de la naturaleza humana. Palabras clave: psicología y la educación; formación de profesores; enseÃ±anza de la psicología.